Doing Unto Others: The Reciprocity of Helping Behavior in Organizations - Deckop, John R. (Journal of business ethics, 2003)
Reciprocity is a fundamental aspect of social life, and a phenomenon studied from a wide variety of philosophical, theological, and social scientific perspectives. In this study, we use social exchange theory to investigate why employees help other employees. We hypothesize, based on the norm of reciprocity (Gouldner, 1960), that a significant cause of an employee's helping behavior is how much organizational citizenship behavior (OCB) the employee has received from coworkers. To provide evidence of the discriminant validity of OCB received as an antecedent of helping behavior, we also assess its effects on another form of extra-role behavior, voice, as well as in-role performance. We found, in a sample of 157 employee-supervisor dyads, that OCB received was related to helping behavior after controlling for several antecedents of helping behavior identified in past research, and was less related to voice and in-role behavior, as hypothesized. Implications for theory and practice are presented.